WALKING FOOTBALL4HEALTH (WAF4H) ASIA – A MOVEMENT TO PROMOTE BETTER HEALTH AND WELLBEING THROUGH SPORT - Heil, Daniel P.; Salle, Dee Dee A. (ASEAN Journal of Sport for Development and Peace, 2021)
Walking Football for Health (WaF4H) Asia is a new movement that exemplifies what the United Nations refers to as sport for development and peace – i.e., programs that use a common community interest in sporting activities to leverage positive change in non-sport development goals. WaF4H Asia is a communities-crossing- countries health empowerment movement. While WaF4H Asia has general goals of impacting the physical, mental, and social well-being of its participants by playing walking football, there is also a steady emphasis on communication and bonding within families and between community members, as well as inclusivity of all who are willing and able to play. To help evaluate the potential impact that playing walking football may have on the WaF4H Asia goals, a quantitative research team was formed. This paper describes the first three international research projects performed by this team that were focused on evaluating the physiological intensity of match play walking football for middle-aged and older adults. The team took advantage of modern electronic monitoring equipment and convenience sampling to determine measures of metabolic, cardiovascular, and walking intensity for entire teams competing in tournaments across the world (Singapore, London, and Perth). The results from these studies consistently showed that measures of both metabolic and cardiovascular intensity exceeded established thresholds (3.0 METs and 65% HRMAX, respectively) that are equivalent to a moderate physiological intensity. Thus, like many other forms of recreational activity and competitive sports, the intensity of match play walking football is great enough to positively impact measures related to changes in physical, mental, and social well-being in middle-aged and older adults. These quantitative results support the use of walking football by WaF4H Asia to promote development and peace with health and fitness.